EVALUATING THE IMMEDIATE EFFECTS OF DEEP PRESSURE ON CHILDREN DEVELOPMENTAL COORDINATION DISORDER: DEMONSTRATING INDIVIDUAL DIFFERENCES - SANKAR U, GANAPATHY; R, MONISHA; VALLABA DOSS, CHRISTOPHER AMALRAJ; RM, PALANIVEL (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: However, every occupational therapist used deep pressure for treating children with developmental coordination disorder (DCD). It has been used widely in the therapy aspect, but there is limited research evaluating the immediate effects of deep pressure. The current study aims to evaluate the immediate effects of deep pressure on children with DCD. Methodology: Pre-test and post-test design was employed; mood and behavior were assessed for 20 children with DCD before and after deep pressure sessions. Results: Five children responded with positive result on all the domains following deep pressure. Four showed positive result on three out of five domains. Sufficient information was available from eight participants. Three showed beneficial results statistically. A non-parametric technique (Tau-U) was used for the analysis. Conclusion: Deep pressure has high relevance to clinical practice and appears to be of immediate benefit to this population with DCD.